RISK MANAGEMENT OF TIME CONTROL ON THE CONSTRUCTION OF SAUMLAKI PORT - Arman Jayady; Edwin Moerdianto (Indonesian Journal of Multidisciplinary Science, 2022)
In the development of the port, there are potentially risk factors that are not identified during its implementation, which can affect work delays and add to unforeseen costs, thus requiring handling in accordance with the classification of risks that occur. The risk is in accordance with the type of activity and the environment of the construction project implemented. The study aims to analyze the influential risk factors during the work carried out, based on the perspective of service providers (consultants and contractors) and owners as well as how to handle risks (mitigation) and the effect of the implementation of the Saumlaki Port Facility Construction work on controlling the timing of work. Identifying risks - risks encountered in the study using the interview method against potential risksthat are likely to occur. The survey results show that there are three risks that have a high risk classification from the perspective of service providers that have the greatest impact on project delays. Theconclusion in the research is the need to apply risk management to the implementation of development to minimize delays and reduce unforeseen costs.